Reaction speed ability of pencak silat athletes: objective measurement using TZ quick-light reaction training - Tarisha Zahra; Ira Purnamasari; Geraldi Novian (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: Pencak silat is a traditional Indonesian martial art that requires optimal mastery of biomotor components, especially reaction speed, which plays an important role in achieving performance during competition. However, reaction training is often difficult to implement due to limited facilities, making it challenging for coaches and athletes to conduct objective evaluations. The novelty of this study lies in the use of the TZ Quick-Light Reaction Training (TZ Quick-LRT) tool as a technology-based instrument to objectively measure athletes’ reaction speed. Purpose: This study aimed to objectively measure the reaction speed of pencak silat athletes using the TZ Quick-LRT tool. Methods: The research employed a descriptive quantitative method involving 20 athletes from the pencak silat student activity unit at Universitas Pendidikan Indonesia. Each athlete completed two measurement sessions, each consisting of eight random LED visual stimuli. The average reaction times were analyzed using descriptive statistics in SPSS version 21 to obtain minimum, maximum, mean, and standard deviation values. Results: The fastest reaction time recorded was 0.712 seconds, while the slowest was 2.842 seconds. Descriptive analysis revealed that the mean reaction time in the first session was 1.510 seconds (SD = 0.238), and in the second session it improved to 1.461 seconds (SD = 0.243), indicating better responses in the second measurement. Conclusion: The TZ Quick-LRT tool proved to be capable of measuring pencak silat athletes’ reaction speed objectively, accurately, and in a data-based manner. The contribution of this research lies in utilizing sports technology as both a training medium and a performance evaluation instrument. The limitation of this study is the tool’s lack of portability. Future research is suggested to develop a more practical device and examine its effectiveness in long-term training programs